Methods for genome assembly and haplotype phasing - LAREAU LIANA F; GREEN JR RICHARD E (2018)
The disclosure provides methods for greatly accelerating and improving de novo genome assembly. The methods disclosed herein utilize methods for data analysis that allow for rapid and inexpensive de novo assembly of genomes from one or more subjects. The disclosure further provides that the methods disclosed herein can be used in a variety of applications, including haplotype phasing, and metagenomics analysis. 本发明提供了用于大大加快并改善从头基因组组装的方法。本文所公开的方法利用数据分析方法，使来自个或多个受试者的基因组的从头组装快速且便宜。本发明进步提供，本文所公开的方法可用于多种应用，包括单体型定相和宏基因组分析。